CTCF genomic binding sites in Drosophila and the organisation of the bithorax complex. - Eimear E Holohan; Camilla Kwong; Boris Adryan; Marek Bartkuhn; Martin Herold; Rainer Renkawitz; Steven Russell; Robert White (PLoS Genetics)
Insulator or enhancer-blocking elements are proposed to play an important role in the regulation of transcription by preventing inappropriate enhancer/promoter interaction. The zinc-finger protein CTCF is well studied in vertebrates as an enhancer blocking factor, but Drosophila CTCF has only been characterised recently. To date only one endogenous binding location for CTCF has been identified in the Drosophila genome, the Fab-8 insulator in the Abdominal-B locus in the Bithorax complex (BX-C). We carried out chromatin immunopurification coupled with genomic microarray analysis to identify CTCF binding sites within representative regions of the Drosophila genome, including the 3-Mb Adh region, the BX-C, and the Antennapedia complex. Location of in vivo CTCF binding within these regions enabled us to construct a robust CTCF binding-site consensus sequence. CTCF binding sites identified in the BX-C map precisely to the known insulator elements Mcp, Fab-6, and Fab-8. Other CTCF binding sites correlate with boundaries of regulatory domains allowing us to locate three additional presumptive insulator elements; "Fab-2," "Fab-3," and "Fab-4." With the exception of Fab-7, our data indicate that CTCF is directly associated with all known or predicted insulators in the BX-C, suggesting that the functioning of these insulators involves a common CTCF-dependent mechanism. Comparison of the locations of the CTCF sites with characterised Polycomb target sites and histone modification provides support for the domain model of BX-C regulation.